the National platform for theses: How to promote Algerian dissertation fund - Nawel MEBTOUCHE (Journal of Science and Knowledge Horizons, 2025)
This study deals with digital academic platforms and their role in promoting Algerian grey literature.  The Research Centre for Scientific and Technical Information (CERIST) has developed the National theses platform.  It’s a national reservoir that allows the collection of the huge amount of theses that are discussed annually in Algerian universities. This paper helps to understand the role of this this digital platform in the management, visibility and protection of Algerian grey literature. To conduct this study, we chose to use a descriptive-analytical approach. It allowed us to know how the platform is managed and the actors involved in it. It has played an effective role in promoting Algerian theses and protecting it from plagiarism. The efforts of all parties and the joint cooperation between CERIST and Algerian academic institutions should be combined in order to notify all topics in progress and deposit all defended theses without exception at the level of the platform.